2019
DOI: 10.5755/j01.itc.48.2.21667
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Control Schemes of Human Response to a Dynamic Virtual 3D Face

Abstract: This paper introduces the application of predictor-based control principles for the control of human response to a virtual 3D face. A dynamic woman 3D face is observed in virtual reality. We use changing distance-between-eyes in a 3D face as a stimulus – control signal. Human responses to the stimulus are observed using EEG-based excitement signals – output signal. The technique of dynamic systems identification which ensure stability and possible higher gain of the model for building a predictive input-output… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…In a related study, Swidrak and Pochwatko (2019) showed a heartrate deceleration of people who are touched by a virtual human. Another facet of human-agent interaction is the role of different facial expressions and how they affect physiological responses (Mueller et al, 2017;Ravaja et al, 2018;Kaminskas and Sciglinskas, 2019).…”
Section: Applications With Agent Interactionmentioning
confidence: 99%
“…In a related study, Swidrak and Pochwatko (2019) showed a heartrate deceleration of people who are touched by a virtual human. Another facet of human-agent interaction is the role of different facial expressions and how they affect physiological responses (Mueller et al, 2017;Ravaja et al, 2018;Kaminskas and Sciglinskas, 2019).…”
Section: Applications With Agent Interactionmentioning
confidence: 99%